ANALYSIS OF INVENTORY AND RAW MATERIAL COST VALUATION USING FIFO, LIFO AND WEIGHTED AVERAGE METHODS - Maria Lapriska Dian Ela Revita; Jumiyati (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Statement of Financial Accounting Standards (PSAK) No. 14 explains inventory issues, including inventory valuation, methods used to record inventory, and inventory reporting. This study aims to calculate the valuation of raw material costs and the value of ending inventory of raw materials using the FIFO, LIFO, and Weighted Average methods. In this paper, the author uses a descriptive qualitative method and Literature Study. Based on the results of the calculation of the three methods in the Case Study of PT.